SIG SEBARAN PRODUKSI PERKEBUNAN KELAPA MENURUT KABUPATEN/KOTA PEMALANG 2018-2020 - Widya Aprilia; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. ADIBA AISHA AMIRA, 2024)
Coconut plantations play an important role in the plantation sector in Indonesia, especially in the Pemalang area. This article analyzes the distribution of coconut plantation production in Pemalang district/city using data on production and area of coconut cultivation based on Pemalang district/city. Production distribution analysis includes statistical methods and geographic mapping to identify coconut production patterns in each administrative region. The results of this analysis provide an overview of the significant differences in coconut production between districts/cities in Pemalang from 2018 to 2020. Apart from that, this analysis also provides an in-depth understanding of the distribution of coconut production in Pemalang District/City and will later become the basis for strategic planning to increase coconut plantation production, improving agricultural practices and improving the welfare of local communities and farmers.